2007
DOI: 10.1186/1476-0711-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Two or more enteropathogens are associated with diarrhoea in Mexican children

Abstract: Background: Diarrhoeal diseases constitute a major public health problem, particularly in the developing world, where the rate of mortality and morbidity is very high. The purpose of this study was to conduct a 2 years and 3 months study in order to determine the prevalence of five enteropathogen diarrheogenic agents in Mexico City.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 34 publications
5
46
1
7
Order By: Relevance
“…Studies in Mexico also recognize the importance of E coli in childhood diarrhoea and in asymptomatic infections. A more recent Mexican case-control study reported that in more than 50% of cases of diarrhoea there was more than one pathogen implicated, including any combination of E. histolytica, Salmonella, or E. coli pathogens [33]. Case-control studies reported from Argentina have concentrated more on STEC, as this country has a high incidence of hemolytic uremic syndrome associated with O157:H7 and non-O157:H7 STEC strains [34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Mexico also recognize the importance of E coli in childhood diarrhoea and in asymptomatic infections. A more recent Mexican case-control study reported that in more than 50% of cases of diarrhoea there was more than one pathogen implicated, including any combination of E. histolytica, Salmonella, or E. coli pathogens [33]. Case-control studies reported from Argentina have concentrated more on STEC, as this country has a high incidence of hemolytic uremic syndrome associated with O157:H7 and non-O157:H7 STEC strains [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown by numerous studies carried out in developing countries (3,10,27) that more than one enteric pathogen can be detected in stool samples of diarrheal patients. Mixed pathogens are identifiable in 12% to 26% of individuals with diarrhea; ETEC and V. cholerae O1 can be isolated together in about 13% of samples from patients with acute watery diarrhea in Bangladesh (5,12,33,40,44).…”
mentioning
confidence: 99%
“…ETEC appears to be endemic in other urban and developing sites of Latin America. 19,24,25,46,47 Differences in epidemic behavior between EIEC and ETEC may be explained by infectious dose and environmental tolerance. EIEC has a lower endpoint on the infectious dose range than ETEC (10 6 -10 10 organisms compared with 10 8 -10 10 ) 2 and thus, amplification of an epidemic through person-to-person transmission may be more likely.…”
Section: Discussionmentioning
confidence: 99%
“…Crosssectional studies of multiple pathotypes suggest that ETEC is the predominant circulating pathotype. 6,[24][25][26][27] However, previous research from northwestern Ecuador suggests that EIEC is the dominant pathogen in this region. 28 Longitudinal data would be important to confirm that these patterns hold over time.…”
Section: Introductionmentioning
confidence: 99%